Early diagnosis of leptospirosis by conventional methods: One-year prospective study - Sharma Krishna; Kalawat Usha (Wolters Kluwer Medknow Publications, 2008)
Several techniques are available for the diagnosis of leptospirosis and microscopic agglutination test is considered as gold standard, but these require sophisticated techniques and instruments. This study was conducted to know the sensitivity and specificity of dark field microscopy (DFM) as compared to IgM enzyme-linked immunosorbent assay (ELISA) in correlation with clinical diagnosis. It is a prospective study of 297 samples received from clinically suspected cases of leptospirosis for DFM and IgM ELISA. We tried to evaluate the easily available technique, DFM. We got promising results with DFM. Specificity and sensitivity were observed to be 61% and 60%, respectively, alone and 95.8% efficacy when combined with IgM ELISA. Thus, DFM should be tried for where other diagnostic tools are not easily available. It is an easy and rapid technique, which can help in the early diagnosis and management of patients